My Four Dogs: Urban Ecology in Vjeran Miladinović Merlinka’s Terezin sin - Filipović, Andrija (Poznańskie Studia Slawistyczne, 2022)
In this article, I analyze the relations between humans, non-humans, and infrastructure in Vjeran Miladinović Merlinka’s fictionalized autobiography Terezin sin. I argue that queer humans and non-humans share a particular ontological and axiological space and time in urban ecology in relation to the built environment of cis-heteronormative socius grounded in reproductive heterosexuality. The fictionalized autobiography that is explored in this article offers a particular view of minoritarian relation as it depicts a queer form of relationality that is lived sideways to the cis-heteronormativity and reproductive heterosexuality as an oppressive form of life that creates a specific kind of infrastructural intimacy for itself in the urban built environment. Relations between queer humans and non-humans under these conditions are decidedly messy, as they are described as both caring and exploitative in Terezin sin.